Investigation of basic psychological needs in physically disabled athletes - Agdum, F.; Alpdogan, S. S. (International Journal of Disabilities Sports and Health Sciences, 2023)
Basic psychological needs are fundamental elements that influence individuals' motivation, performance, and overall well-being. These needs reside at the core of human behavior and constitute factors that determine individuals' psychological health and satisfaction. The purpose of this study is to examine the satisfaction and frustration of basic psychological needs among physically disabled athletes across various variables. A total of 128 athletes, including 68 males and 60 females in sitting volleyball and wheelchair basketball participated in the research. In the current study, to assess the satisfaction and frustration of basic psychological needs, the 'Psychological Need States in Sports Scale' was employed. Data collected via Google Forms were converted into the appropriate file format by the researchers and relevant hypothesis tests were applied using the JASP 0.15.0.0 statistical analysis software. In the autonomy satisfaction subscale, it was determined that male athletes (5.25 ± 2.26) obtained higher scores compared to female athletes (4.42 ± 1.99) (p<.05). In the competence frustration and relatedness frustration subscales, there is a statistically significant difference in favor of male athletes (p<.05). In the competence satisfaction and relatedness satisfaction subscales, the mean scores of first division athletes are significantly higher than those of the other group (p<.05). Moreover, in the competence frustration and relatedness frustration subscales, the scores of second division athletes are statistically significantly higher than those of the other group (p<.05). As conclusion, it can be stated that male and first - division physically disabled athletes have a higher level of satisfaction with their basic psychological needs.